2018
DOI: 10.1590/1981-22562018021.170187
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and time since diagnosis of Diabetes Mellitus among the elderly

Abstract: Objectives: To evaluate the quality of life of the elderly with Diabetes Mellitus and to relate the time since diagnosis of diabetes with the quality of life of elderly persons receiving care at a basic health unit. Method: A cross-sectional quantitative study carried out in a Basic Health Unit with 196 elderly persons. For data collection, three instruments were used: one structured (sociodemographic and clinical variables) and the Whoqol-bref and Whoqol-old, with scores ranging from 0 to 100. Descriptive sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 19 publications
3
23
0
17
Order By: Relevance
“…Foram entrevistadas 51 pessoas com diabetes e deficiência visual, com predominância do sexo masculino (58%), idade igual ou superior a 60 anos (43,1%), idade média de 54 anos e desvio padrão de 16,3 anos. Esses resultados foram semelhantes ao estudo realizado no Distrito Federal com pessoas com diabetes, o qual também constatou predomínio do sexo masculino, idade entre 60 e 70 anos, que possuíam alteração visual 11 .…”
Section: Resultsunclassified
“…Foram entrevistadas 51 pessoas com diabetes e deficiência visual, com predominância do sexo masculino (58%), idade igual ou superior a 60 anos (43,1%), idade média de 54 anos e desvio padrão de 16,3 anos. Esses resultados foram semelhantes ao estudo realizado no Distrito Federal com pessoas com diabetes, o qual também constatou predomínio do sexo masculino, idade entre 60 e 70 anos, que possuíam alteração visual 11 .…”
Section: Resultsunclassified
“…A study conducted by Anindyati (2013) in Budiarti (2018) found that the function of pancreatic beta cells in patients with old diabetes has been damaged. The results of a study conducted by Lima et al (2018) also stated that T2DM patients with a long diagnosis duration, such as more than ten years, their body health function decreases faster so that the quality of life they get is lower. 6.…”
Section: The Effect Of the Time Period Of Diag-mentioning
confidence: 99%
“…< 1 sebanyak 1 orang (2,2%), 1 -4 tahun sebanyak 34 orang (73,9%), 5-10 tahun sebanyak 9 (19,6%) responden serta responden dengan lama menderita DM tipe 2 lebih dari 10 tahun sebanyak 2(4,3%) responden. Sejalan dengan penelitian (Lima et al, 2018) bahwa dalam surveinya dia menyatakan bahwa pasien dengan DM yang menderita DM selama lebih dari 10 tahun, terutama pada lansia memiliki skor kualitas hidup terburuk terutama dalam aspek fisik , hubungan sosial, independensi dan partisipasi sosial.…”
Section: Karakteristik Pasien Prolanis DI Puskesmasunclassified